2009
DOI: 10.1111/j.1464-410x.2008.08306.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening by lower urinary tract symptoms vs asymptomatic prostate‐specific antigen levels leading to radical prostatectomy in Danish men: tumour characteristics and treatment outcome

Abstract: OBJECTIVE To compare the tumour characteristics and treatment outcome in men undergoing radical prostatectomy (RP) for prostate cancer diagnosed with or with no lower urinary tract symptoms (LUTS). PATIENTS AND METHODS In Denmark, prostate‐specific antigen (PSA) testing is recommended only in men with a family history of prostate cancer, or those with LUTS that could be caused by prostate cancer. However, increasingly many men undergoing RP are asymptomatic and are diagnosed as a result of unsystematic PSA scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Our study was limited by a lack of important clinical information about the indication for testing but previous studies find that opportunistic screening in Denmark is ubiquitous even though guidelines advice otherwise . Another limitation was that we had only practice identification numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was limited by a lack of important clinical information about the indication for testing but previous studies find that opportunistic screening in Denmark is ubiquitous even though guidelines advice otherwise . Another limitation was that we had only practice identification numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was limited by a lack of important clinical information about the indication for testing but previous studies find that opportunistic screening in Denmark is ubiquitous even though guidelines advice otherwise. 31 Another limitation was that we had only practice identification numbers. PSA test rates from partnership practices are a mix of two or more general practitioners, but our results were consistent when looking only at single-handed practices.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…Nevertheless, increased non-systematic use of PSA during the past decade has led to a marked rise in the incidence of prostate cancer also in Denmark 26 . A recent study showed that 35% of patients treated by radical prostatectomy in Denmark between 1997 and 2008 had been referred without prostate-related symptoms 27 , and in a Swedish study 28% of prostate cancer cases diagnosed in 2005 were based on PSA testing during health examinations 28 . An impact of opportunistic screening should therefore also be considered in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2004 telephone survey of over 700 Korean men older than 50 years in a small city, approximately 15% had been screened for PCa during the previous 2 years (unpublished data), a much lower rate than the 75% reported for men in the United States [16]. In view of the growing proportion of asymptomatic PCa, we suggest that PSA screening is needed not only in men with LUTS that could be caused by PCa, but also in men who are asymptomatic at baseline [17,18]. …”
Section: Discussionmentioning
confidence: 99%